The effect of the Lola Speak application on students’ pronunciation skills - Tara Arini; Yani Lubis (Universitas Pendidikan Indonesia, 2025)
The integration of Mobile-assisted Language Learning (MLL) tools, such as the Lola Speak app, offers an innovative pathway to improving English pronunciation skills. This study aims to investigate the effectiveness of Lola Speak in improving students’ pronunciation. The rationale for this study lies in the persistent challenges faced by learners in acquiring accurate pronunciation using traditional methods, which often lack interactivity and real-time feedback. This study used a quantitative approach with a quasi-experimental pre-test and post-test design. The sample consisted of 60 high school and university students in Medan, divided into an experimental and a control group. Quantitative data were analyzed using paired t-tests to measure improvement within each group, and independent two-sample t-tests to compare results between groups, with a significance level of 0.05. The results showed a significant improvement in the experimental group's pronunciation ability compared to the control group. These findings suggest that the use of mobile applications such as Lola Speak positively contributes to the improvement of English pronunciation ability. Thus, this application can be an effective supporting resource in English learning in the digital era. Abstrak Integrasi alat pembelajaran bahasa berbantuan seluler (Mobile-assisted Language Learning atau MALL), seperti aplikasi Lola Speak, menawarkan jalur inovatif untuk meningkatkan keterampilan pengucapan bahasa Inggris. Penelitian ini bertujuan untuk menyelidiki efektivitas Lola Speak dalam meningkatkan pengucapan siswa. Dasar pemikiran penelitian ini terletak pada tantangan terus-menerus yang dihadapi oleh pelajar dalam memperoleh pengucapan yang akurat menggunakan metode tradisional, yang sering kali kurang interaktivitas dan umpan balik waktu nyata. Penelitian ini menggunakan pendekatan kuantitatif dengan desain kuasi-eksperimental pre-test dan post-test. Sampel terdiri dari 60 siswa di SMA dan universitas di Medan yang dibagi ke dalam kelompok eksperimen dan kontrol. Data kuantitatif dianalisis menggunakan uji t berpasangan untuk mengukur peningkatan dalam setiap kelompok, dan uji t dua sampel independen untuk membandingkan hasil antar kelompok, dengan tingkat signifikansi 0,05. Hasil menunjukkan peningkatan yang signifikan dalam kemampuan pelafalan kelompok eksperimen dibandingkan kelompok kontrol. Temuan ini menunjukkan bahwa penggunaan aplikasi mobile seperti Lola Speak berkontribusi positif terhadap peningkatan kemampuan pelafalan bahasa Inggris. Dengan demikian, aplikasi ini dapat menjadi sumber daya pendukung yang efektif dalam pembelajaran bahasa Inggris di era digital. Kata Kunci: Lola Speak; pelafalan; pembelajaran bahasa berbantuan seluler